The dental perspective on osteogenesis imperfecta in a Danish adult population - Kirstine Juhl Thuesen; Hans Gjørup; Jannie Dahl Hald; Malene Schmidt; Torben Harsløf; Bente Langdahl; Dorte Haubek (BMC, 2018)
Abstract Background To report on dental characteristics and treatment load in Danish adult patients with osteogenesis imperfecta (OI). Methods Oral examination of 73 patients with OI was performed and OI type I, III, and IV were represented by 75.3%, 8.2%, and 16.4%, respectively. Patients were diagnosed as having dentinogenesis imperfecta (DI) if they had clinical and radiological signs of DI. In the data analysis, mild OI (type I) was compared to moderate-severe OI (type III and IV). Results Discoloration of teeth was prevalent in patients with moderate-severe compared to mild OI (83.3% vs. 5.5%, p < 0.001). Cervical constriction and pulpal obliteration were frequent findings in patients with moderate-severe OI (61.1% and 88.9%, respectively), whereas pulp stones and taurodontism were diagnosed in patients with mild OI only (29.1% and 9.1%, respectively). DI was found in 24.7% of OI patients and considerably more frequent in patients with moderate-severe (94.4%) compared to mild OI (1.8%) (p < 0.001). The number of teeth with artificial crowns was significantly higher in patients with moderate-severe OI than in patients with mild OI (median 1.5, range 0-23 vs. median 0, range 0-14) (p < 0.001). The number of teeth with fillings in patients with mild OI was significantly higher than in patients with moderate-severe OI (mean 9.7, SD 5.1, median 9.0, range 1-21 vs. mean 5.0, SD 4.4, median 4.0, range 0-16) (p < 0.001). Conclusions One fourth of patients with OI had DI, and the vast majority of them had moderate-severe OI. Whereas discoloration of teeth, cervical constriction and pulp obliteration were frequent findings in patients with moderate-severe OI, pulp stones and taurodontism were found in patients with mild OI only. In patients with moderate-severe OI, the dental treatment load was dominated by prosthetic treatment, whereas restorative treatment with fillings was more prevalent in patients with mild OI.